2015
DOI: 10.1073/pnas.1505753112
|View full text |Cite
|
Sign up to set email alerts
|

MINCR is a MYC-induced lncRNA able to modulate MYC’s transcriptional network in Burkitt lymphoma cells

Abstract: Despite the established role of the transcription factor MYC in cancer, little is known about the impact of a new class of transcriptional regulators, the long noncoding RNAs (lncRNAs), on MYC ability to influence the cellular transcriptome. Here, we have intersected RNA-sequencing data from two MYC-inducible cell lines and a cohort of 91 B-cell lymphomas with or without genetic variants resulting in MYC overexpression. We identified 13 lncRNAs differentially expressed in IG-MYC-positive Burkitt lymphoma and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
99
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 76 publications
3
99
0
Order By: Relevance
“…1F). The role of MINCR in Burkitt lymphoma cells has been studied by others research team [13]. Whether MINCR was regulated by c-myc in GBC cells has never been reported before.…”
Section: Mincr Levels Are Overexpressed In Gbc Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…1F). The role of MINCR in Burkitt lymphoma cells has been studied by others research team [13]. Whether MINCR was regulated by c-myc in GBC cells has never been reported before.…”
Section: Mincr Levels Are Overexpressed In Gbc Tissuesmentioning
confidence: 99%
“…Thus, with the advancement of new technology, further studies about the relation between MYC and LncRNAs are being carry out [11,12]. MYC-induced long non-coding RNA (MINCR) is a newly defined LncRNA that is reported to be correlated with MYC expression in MYC-positive lymphomas [13]. To our knowledge, there is no published literature about MINCR in other cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Myc-induced long noncoding RNA (MINCR) has been recently identifi ed as a c-Myc-inducible lncRNA [ 98 ]. MINCR has a strong correlation with c-Myc expression in cancer.…”
Section: Mincrmentioning
confidence: 99%
“…Since c-Myc is upregulated in many human cancers it is subject to intense investigation for cancer treatment [15, 16]. Several studies have shown that c-Myc regulates the expression of long ncRNAs, and that some of these transcripts can participate in the transcriptional functions mediated by c-Myc [19-22]. Long ncRNA-mediated regulation of translation of c-Myc has also been suggested [23, 24].…”
Section: Introductionmentioning
confidence: 99%